1993
DOI: 10.1002/bjs.1800800943
|View full text |Cite
|
Sign up to set email alerts
|

Role of early and extensive surgery in the treatment of severe necrotizing soft tissue infection

Abstract: Forty-two patients with necrotizing soft tissue infection are reviewed. Bacterial culture revealed between two and seven types of micro-organism in each patient. All patients were treated with radical surgical debridement and a combination of antibiotics. In 30 patients, early diagnosis and treatment resulted in only two deaths. Delayed surgical intervention in 12 patients transferred from outside hospitals was followed by nine deaths. Predisposing factors and site of infection did not affect outcome. Of 26 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
0
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(85 citation statements)
references
References 7 publications
3
77
0
5
Order By: Relevance
“…Delayed recognition is a key factor when considering the high mortality. 6 Imaging modalities such as computed tomography, magnetic resonance imaging and frozen section biopsy have been previously used in the discrimination between necrotising fasciitis and other soft tissue infections but these methods have been limited by cost and availability. 2,7,8 The Laboratory Risk Indicator for Necrotising Fasciitis (LRINEC) is a clinical tool first described by Wong C et al 9 The tool is based on six common serum parameters at the time of presentation: C-reactive protein (CRP), total white cell count, haemoglobin, serum sodium, creatinine and glucose (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Delayed recognition is a key factor when considering the high mortality. 6 Imaging modalities such as computed tomography, magnetic resonance imaging and frozen section biopsy have been previously used in the discrimination between necrotising fasciitis and other soft tissue infections but these methods have been limited by cost and availability. 2,7,8 The Laboratory Risk Indicator for Necrotising Fasciitis (LRINEC) is a clinical tool first described by Wong C et al 9 The tool is based on six common serum parameters at the time of presentation: C-reactive protein (CRP), total white cell count, haemoglobin, serum sodium, creatinine and glucose (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, studies have shown an association between time to intervention and patient survival for those diagnosed with an NSTI [4][5][6]. Wheras a number of adjuvant therapies have been proposed-including specific therapies targeting bacterial toxins such as intravenous gamma globulin [7,8], plasmapheresis [9], and activated protein C [10,11] and the more generalized therapy of hyperbaric oxygen therapy (HBOT) [12,13]-there have been no universally accepted changes in the management of NSTI over the last three decades.…”
mentioning
confidence: 99%
“…4 microbes per wound culture were detected. Voros D. 12 (1993) reviewed 43 patients of necrotizing soft tissue infection and he found that bacterial culture revealed 2-7 microbes in each patient.…”
Section: Bacteriologymentioning
confidence: 99%
“…66% but those patients who were operated after 5 days the mortality was 33%. Voros D. 12 (1993) reviewed 45 patients with necrotizing soft tissue infection and found that in 30 patients early diagnosis and treatment resulted in only 2 deaths and delayed surgical intervention in 12 patients was followed by 9 deaths.…”
Section: Mortality and Related Comorbid Conditionsmentioning
confidence: 99%